Case Report: A Novel GJB2 Missense Variant Inherited From the Low-Level Mosaic Mother in a Chinese Female With Palmoplantar Keratoderma With Deafness - Tian, Xinyuan; Zhang, Chuan; Zhou, Bingbo; Chen, Xue; Feng, Xuan; Zheng, Lei; Wang, Yupei; Hao, Shengju; Hui, Ling (Frontiers in Genetics, 2022)
Dominant variants in the gap junction beta-2 (GJB2) gene may lead to various degrees of syndromic hearing loss (SHL) which manifest as sensorineural hearing impairment and hyperproliferative epidermal disorders, including palmoplantar keratoderma with deafness (PPKDFN). So far, only a few GJB2 dominant variants causing PPKDFN have been discovered. Through the whole-exome sequencing (WES), a Chinese female patient of PPKDFN with severe palmoplantar hyperkeratosis and delayed-onset hearing loss has been identified. She had a novel heterozygous variant, c.224G>C (p.R75P), in the GJB2 gene, which was unreported previously. The proband's mother who had mild phenotype was suggested the possibility of mosaicism by WES (~120×), and the ultra-deep targeted sequencing (~20,000×) was used for detecting low-level mosaic variants which provided accurate recurrence-risk estimates and genetic counseling. In addition, the analysis of protein structure indicated that the structural stability and permeability of the connexin 26 (Cx26) gap junction channel may be disrupted by the p.R75P variant. Through retrospective analysis, it is detected that the junction of extracellular region-1 (EC1) and transmembrane region-2 (TM2) is variant hotspot for PPKDFN, such as p.R75. Our report reflects the important and effective diagnostic role of WES in PPKDFN and low-level mosaicism, expands the spectrum of the GJB2 variant, furthermore, provides strong proof about the relevance between the p.R75P variant in GJB2 and PPKDFN.